1991
DOI: 10.1152/ajpheart.1991.260.2.h362
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia- or hyperoxia-induced changes in arteriolar vasomotion in skeletal muscle microcirculation

Abstract: Arteriolar vasomotion was characterized in the skin muscle of the unanesthetized hamster skinfold window preparation and related to the specific arterioles that give rise to the different types of activity. The arterioles were classified according to the Strahler method: order 0 was assigned to capillaries and order 4 to the largest arterioles. The arterioles showed vasomotion with a specific range of frequencies that varied according to the vessel order; the highest fundamental frequency (9.1 +/- 3.9 cycles/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 0 publications
4
81
0
3
Order By: Relevance
“…13͑d͒ and 13͑e͔͒ suggested that arteriole A1 had a more significant vasomotion than did V1 under hyperoxia but with a similar oscillation frequency of ϳ1.6 cycles/ min ͑cpm͒, which is in good agreement with the observation from a previous invasive study. 112 By isolating the vasodilation effect, an increase of 96Ϯ 3% in the arteriolar diameter and 26Ϯ 5% in the venular diameter under hypoxia was observed ͓Fig. 13͑c͔͒, which agrees with a scanning laser fluorescent ophthalmoscopy study.…”
Section: Microhemodynamic Monitoringsupporting
confidence: 87%
“…13͑d͒ and 13͑e͔͒ suggested that arteriole A1 had a more significant vasomotion than did V1 under hyperoxia but with a similar oscillation frequency of ϳ1.6 cycles/ min ͑cpm͒, which is in good agreement with the observation from a previous invasive study. 112 By isolating the vasodilation effect, an increase of 96Ϯ 3% in the arteriolar diameter and 26Ϯ 5% in the venular diameter under hypoxia was observed ͓Fig. 13͑c͔͒, which agrees with a scanning laser fluorescent ophthalmoscopy study.…”
Section: Microhemodynamic Monitoringsupporting
confidence: 87%
“…It is possible that the vasomotion may reflect local autoregulatory responses to DEA/NO-induced hypotension, lowered TBF and hypoxia. Induction of vasomotor activity in normal arterioles has previously been reported in response to reduction in systemic pressure as well as reduction in oxygenation (Bertuglia et al, 1991;Vollmar et al, 1994). However, the effect seems to be controlled at the tissue level, rather than by systemic factors.…”
Section: Discussionmentioning
confidence: 90%
“…Under in vitro conditions, moderate hypoxia has been shown to inhibit L-type Ca 2ϩ channels in arterial smooth muscle cells leading to a decrease in intracellular Ca 2ϩ , promoting muscle relaxation without vasomotion (5). In contrast, in the hamster skeletal microcirculation, moderate to severe hypoxia has been shown to increase the frequency of arteriolar rhythmic diameter changes (2). Increased flow motion was suppressed by phentolamine, a selective ␣-adrenoceptor blocker (4).…”
Section: Discussionmentioning
confidence: 99%